Nauczanie hybrydowe we współczesnej organizacji - Głowicki, Piotr; Łasiński, Gabriel (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
It is well known that contemporary organization must be a learning organization. However the important requirement of organization development is not only knowledge absorbing, but also knowledge creation. Organization must secure a number of conditions to initiate processes of knowledge creation. Those conditions are: specific organization needs, promoting organizational culture, resources as well as specific environment needs. Blended Learning System can be a toll to implicate and accelerate processes of organization knowledge management, and organization knowledge creation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 142-149